Auditory Processing of Non-speech Stimuli by Children in Dual-Language Immersion Programs - Jones, Chloe; Collin, Elizabeth; Kepinska, Olga; Hancock, Roeland; Caballero, Jocelyn; Zekelman, Leo; Vandermosten, Maaike; Hoeft, Fumiko (Frontiers in Psychology, 2021)
Perception of low-level auditory cues such as frequency modulation (FM) and rise time (RT) is crucial for development of phonemic representations, segmentation of word boundaries, and attunement to prosodic patterns in language. While learning an additional language, children may develop an increased sensitivity to these cues to extract relevant information from multiple types of linguistic input. Performance on these auditory processing tasks such as FM and RT by children learning another language is however, unknown. Here we examine 92 English-speaking 7-8-year-olds in the U.S. and their performance in FM and RT perceptual tasks at the end of their second year in Cantonese or Spanish dual-language immersion compared to children in general English education programs. Results demonstrate that children in immersion programs have greater sensitivity to FM, but not RT, controlling for various factors. The immersion program students were also observed to have better phonological awareness performance. However, individual differences in FM sensitivity were not associated with phonological awareness, a pattern typically observed in monolinguals. These preliminary findings suggest a possible impact of formal language immersion on low-level auditory processing. Additional research is warranted to understand causal relationships and ultimate impact on language skills in multilinguals.